Novel route for in-situ H2O2 generation from selective reduction of O-2 by hydrazine using heterogeneous Pd catalyst in an aqueous medium - Choudhary, Vasant R.; Samanta, C.; Jana, Prabhas (Chemical Communications, 2005)
Hydrogen peroxide in high yields can be generated with high efficiency at mild conditions (25 degrees C and atmospheric pressure) with the formation of only environment-friendly by-products (N-2 and H2O) by a reduction of O-2 by hydrazine from its hydrate/salt with its complete conversion in a short reaction period (<= 0.5 h) using a easily separable supported Pd catalyst (Pd/Al2O3, Pd/Ga2O3 or Pd/C) in an acidic aqueous medium in the presence of bromide anions; the presence of both acid (protons) and bromide anions is essential for the selective reduction of O-2 by hydrazine to H2O2 and in their absence, the reaction leads only to the formation of water.

Non-catalytic pyrolysis of ethane to ethylene in the presence of CO2 with or without limited O-2 - Choudhary, Vasant R.; Mondal, Kartick C.; Mulla, Shafeek Abdul Rashid (Journal of Chemical Science, 2006)
Influence of the presence Of CO2, which is a mild oxidant, on the performance of the thermal cracking of ethane to ethylene in the absence or presence of limited O-2 at different temperatures (750-900 degrees C), space velocities (1500-9000 h(-1)) and CO2/C2H6 and O-2/C2H6 mole ratios (0-2.0 and 0-0.3 respectively) has been investigated. In both the presence and absence of limited 02, ethane conversion increases markedly because of the presence Of CO2, indicating its beneficial effect on the ethane to ethylene cracking. The increased ethane conversion is, however, not due to the oxidation of ethane to ethylene by CO2; the formation of carbon monoxide in the presence Of CO2 is found to be very small. It is most probably due to the activation of ethane in the presence Of CO2.
Keywords: ethane; ethane cracking in presence Of CO2; ethane cracking in presence of CO2 and limited O-2; Ethylene; thermal cracking of ethane

Nano-gold supported on Fe2O3: a highly active catalyst for low temperature oxidative destruction of methane green house gas from exhaust/waste gases - Choudhary, Vasant R.; Patil, V. P.; Jana, Prabhas; Uphade, B. S. (Applied Catalysis A-General, 2008)
A number of nano-gold catalysts were prepared by depositing gold on different metal oxides (viz. Fe2O3, Al2O3, Co3O4, MnO2, CeO2, MgO, Ga2O3 and TiO2), using the homogeneous deposition precipitation (HDP) technique. The catalysts were evaluated for their performance in the combustion of methane (1 mol% in air) at different temperatures (300-600 degrees C) for a GHSV of 51,000 h(-1). The supported nano-gold catalysts have been characterized for their gold loading (by ICP) and gold particle size (by TEM/HRTEM or XRD peak broadening). Among these nano-gold catalysts, the Au/Fe2O3 (Au loading = 6.1% and Au particle size = 8.5 nm) showed excellent performance. For this catalyst, temperature required for half the methane combustion was 387 degrees C, which is lower than that required for Pd(1%)/Al2O3 (400 degrees C) and Pt(1%)/Al2O3 (500 degrees C) under identical conditions. A detailed investigation on the influence of space velocity (GHSV = 10,000-100,000 cm(3) g(-1) h(-1)) at different temperatures (200-600 degrees C) on the oxidative destruction of methane over the Au/Fe2O3 catalyst has also been carried out. The Au/Fe2O3 catalyst prepared by the HDP method showed much higher methane combustion activity than that prepared by the conventional deposition precipitation (DP) method. The XPS analysis showed the presence of Au in the different oxidation states (Au-0, Au1+ and Au3+) in the catalyst. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Au/Fe2O3; Deposition precipitation; Homogeneous deposition precipitation; Methane combustion; Supported nano-gold catalysts